Longitudinal assessment of neuronal 3D genomes in mouse prefrontal cortex - Mitchell, Amanda C. (Nat Commun, 2016)
Neuronal epigenomes, including chromosomal loopings moving distal cis-regulatory elements into proximity of target genes, could serve as molecular proxy linking present-day-behaviour to past exposures. However, longitudinal assessment of chromatin state is challenging, because conventional chromosome conformation capture assays essentially provide single snapshots at a given time point, thus reflecting genome organization at the time of brain harvest and therefore are non-informative about the past. Here we introduce ‘NeuroDam' to assess epigenome status retrospectively. Short-term expression of the bacterial DNA adenine methyltransferase Dam, tethered to the Gad1 gene promoter in mouse prefrontal cortex neurons, results in stable G(methyl)ATC tags at Gad1-bound chromosomal contacts. We show by NeuroDam that mice with defective cognition 4 months after pharmacological NMDA receptor blockade already were affected by disrupted chromosomal conformations shortly after drug exposure. Retrospective profiling of neuronal epigenomes is likely to illuminate epigenetic determinants of normal and diseased brain development in longitudinal context.